2002
DOI: 10.1074/jbc.m105902200
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Role of CD80 and CD86 in the Regulation of the Activation of B Cell and B Cell Lymphoma

Abstract: To date, not much has been known regarding the role of CD80 and CD86 molecules in signaling of B cells. The CD28/CTLA4 ligands, CD80 (B7-1) and CD86 (B7-2), are expressed on the surface of freshly isolated splenic B cells, and their expression is up-regulated by lipopolysaccharides. In the present study, we have investigated whether signaling via CD80/CD86 could alter the proliferation and immunoglobulin synthesis of B cells. Splenic B cells were stimulated with lipopolysaccharides in the presence of anti-B7-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
207
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 215 publications
(221 citation statements)
references
References 50 publications
13
207
0
1
Order By: Relevance
“…Previous data also indicated that the amount of IgG1 protein produced by CD40L/IL-4-activated B cells is increased further when CD86 (16,26) and/or ␤ 2 AR (16) are costimulated on the B cell. However, the mechanism responsible for mediating the latter enhancing effect was unknown.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Previous data also indicated that the amount of IgG1 protein produced by CD40L/IL-4-activated B cells is increased further when CD86 (16,26) and/or ␤ 2 AR (16) are costimulated on the B cell. However, the mechanism responsible for mediating the latter enhancing effect was unknown.…”
Section: Discussionmentioning
confidence: 88%
“…Although these findings were attributed to a lack of CD28 costimulation on the Th2 cell that resulted in a decrease in the level of IL-4 and CD40L costimulation provided to the B cell, these findings also suggested that CD86 costimulation might generate a signal within the B cell to regulate the level of a Th celldependent Ab response. Recent in vitro data show that the stimulation of CD86 on a B cell activated through CD40 and the IL-4R with or without BCR stimulation increases the level of IgG1 and IgE produced (16,25) and differentially affects the level of antiapoptotic and proapoptotic molecules expressed (26). Likewise, both host and donor B cells from chimeric mice that received donor cells from CD80/CD86-deficient mice and were challenged with a protein Ag were able to produce Ag-specific IgG1, but the level of IgG1 produced by the CD80/CD86-deficient cells was decreased compared with that of the host B cells (27).…”
Section: Selective Regulation Of Mature Igg1 Transcription By Cd86mentioning
confidence: 99%
“…Several studies have shown the importance of reverse signaling through B7 molecules in various immune cells [39][40][41]. Nevertheless, the molecules involved and consequences of reverse signaling remain elusive.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that plate-bound CTLA4Fc alone could mimic iTreg cell function in controlling DC maturation cannot be reconciled by these models. Therefore, we propose that a cell-extrinsic model of CTLA4 function operates not only by the direct removal of costimulatory molecule from APCs, which requires persistent T cell-DC interaction, but also via triggering reverse signaling in CD80/CD86-expressing DCs.Several studies have shown the importance of reverse signaling through B7 molecules in various immune cells [39][40][41]. Nevertheless, the molecules involved and consequences of reverse signaling remain elusive.…”
mentioning
confidence: 99%
“…6,38,39 Our data are important because they emphasize that co-stimulatory molecules play a pivotal role in APC-mediated immune responses, particularly T-cell activation and proliferation. [40][41][42][43][44][45] In the study herein, we demonstrate the ability of autologous exosomes to be taken up by peripheral monocytes and DCs. Further, they have the potential to modulate the expression of co-stimulatory molecules on APCs from patients with PBC.…”
Section: Discussionmentioning
confidence: 91%